Outcome of Surgery for the Management of High Perianal Fistulae Using Elastic Seton: Elastic Seton Outcomes in High Anal Fistula - Jamil, Tayyaba; Islam, Muzammal; Jan, Mohammad Amir; Nazir, Absar (Pakistan Journal of Health Sciences, 2025)
High perianal fistulae are complex infections often originating from anal glands, requiring sphincter-preserving surgical approaches. Elastic seton offers controlled tract closure with reduced need for postoperative adjustments compared to traditional cutting setons. Objectives: To evaluate the outcomes of elastic seton in managing high perianal fistulae, focusing on pain, healing, hospital stay, and continence preservation. Methods: This descriptive case series was conducted from February 2025 to May 2025 at the Department of Surgery, Surgical Unit III, Sir Ganga Ram Hospital, Lahore. Forty-five patients with high perianal fistulae were enrolled using consecutive non-probability sampling. An elastic seton from a latex glove was placed under spinal anesthesia. Follow-ups at 1 week, 4 weeks, 3, and 6 months assessed pain (VAS), wound healing, complications, and analgesic use. Data were analyzed with SPSS v24.0 using Chi-square and ANOVA, with p < 0.05 significant. Results: Of the 45 patients (64.4% male; mean age 31.3 ± 8.4 years), the mean symptom duration was 11.8 ± 4.1 weeks, and average seton cut-through time was 6.3 ± 0.9 weeks. VAS scores significantly decreased from 5.13 (Week 1) to 0.40 (6 months) (p < 0.001). Complete wound healing occurred in 82.2% of patients, while complications declined from 42.2% to 17.8%. Conclusion: Elastic cutting seton with staged fistulotomy ensured safe, effective high anal fistula management with reduced pain, rapid healing, and preserved continence.